The internet in Cyprus 2014, Final Report - Stylianou, Stelios; Milioni, Dimitra L. (Department of Communication and Internet Studies, Cyprus University of! Technology, 2015)
Internet use has been rising steadily in both communities in Cyprus over the last few years. In 2014, roughly two thirds of the total population aged 15 and over in both communities have been using the internet. The main reasons for not using the internet were lack of interest and lack of technical knowledge. Almost all Greek-Cypriot users connect to the internet at home, about three out of four Greek-Cypriot users who are employed connect to the internet at work and about two thirds of Greek-Cypriot users who are students do so at school. Among Turkish-Cypriots, almost all users connect to the internet at home and almost all users also connect from other locations, including almost all employees who connect at work and almost all students who connect at school. About one third of Turkish-Cypriot users also connect on the move (vs only about one eighth of Greek-Cypriot users). The most popular means to connect to the internet is the computer: more than 90% of users in both communities declared connecting to the internet this way. About two thirds of Greek-Cypriot users and more than 90% of Turkish-Cypriot users connect to the internet from their phones. The upward change in both communities with respect to the use of mobile phones has been dramatic in the last two years. Tablets and e-readers remain less popular. The gap in internet use between residents of urban and residents of rural areas remains visible, yet not very large, in both communities: urbanites use the internet more than rural residents. The same applies to the gender divide: men connect to the internet more than women in both communities in all years. Internet use seems to decrease with age and increase with educational attainment. The use of the internet is also more prevalent among students, as compared to people who are employed or unemployed, housewives or househusbands and the retired. An almost linear positive association occurs in the relationship between income and internet use. The presence of children under 18 years of age in the household is also positively associated with internet use in both communities. Internet use differs between members and non-members in various organizations: more use is observed among Greek-Cypriot members of cultural, professional, political, environmental and sport or recreation organizations and among Turkish-Cypriot members of environmental and sport or recreation organizations, while less use is observed among Greek-Cypriot and Turkish-Cypriot members of religious organizations and Turkish-Cypriot members of political organizations. Clear majorities in all years and in both communities believe that the internet is an important or very important source of information. Similar results were obtained for the importance of television as a source of information. Turkish-Cypriots seem to value newspapers as an important source of information at significantly greater percentages compared to Greek-Cypriots. Results for the radio as a source of information are similar to those for newspapers; yet, slight majorities in both communities do believe that this medium is important or very important in this respect. Respondents in both communities seem to trust interpersonal sources for information, with clear majorities reporting that these sources are important or very important. When it comes to importance as sources of entertainment, the internet and television produced similar results to those about importance for information. Newspapers are generally not regarded as sources of entertainment. The radio falls somewhere in the middle of the distance between internet and television at the one end and newspapers at the other. Among the various social uses of the internet addressed in the questionnaires, using the internet to maintain relationships with family and with friends are the most prevalent in both communities. Using the internet to expand professional or occupational ties is also very popular, especially in the Turkish-Cypriot community. Of lower prevalence is the use of the internet to meet different people (people from different occupations, of different social statuses, of different lifestyles or from different cultures) and to maintain relationships with people with similar political views. The internet is not a very popular means to connect with political parties, NGOs or public officials or to join protest or other social movements. Electronic mail remains the most prevalent online communicative activity, closely followed by instant messaging, especially in recent years. The prevalence of internet phone calls has also approached that of the e-mail and instant messaging in 2014, more so in the Turkish-Cypriot community. Also quite popular is posting messages or comments on discussion boards or forums, as well as posting messages or comments on social networking sites, posting one's own content and reposting or sharing links or content posted by others, especially in the Turkish-Cypriot community in 2014. Regarding using the internet for obtaining various kinds of information, looking for news is the most prevalent activity (with the exception of the Turkish-Cypriot community in 2014). Looking for travel, health and product information remain relatively popular as well, followed by reading blogs. With the exception of using online bank services in the Greek-Cypriot community in all waves and in the Turkish-Cypriot community in 2012 and using the internet to compare prices of products or services in the Greek-Cypriot community in 2014, the rest online transactions addressed in the survey (buying things online, making travel reservations or bookings, paying bills, making online investments and online selling) remain quite low in frequency. The most popular entertainment activities on the internet are playing games, downloading or listening to music, downloading or watching music videos, surfing or web browsing and visiting social networking sites. Looking for jokes, cartoons or other humorous content and listening to online radio stations are also quite popular. The participants reported less frequent use of the internet for looking at religious or spiritual sites, betting, gambling or entering sweepstakes and for looking at sites with sexual content. Regarding using the internet for educational purposes, looking up word definitions and fact checking are quite prevalent and frequent, especially in the Turkish- Cypriot community in 2014. Getting information about school-related work is less prevalent. Distance learning is also quite low in prevalence. Greek-Cypriot users progressively grow more skeptical about the reliability of information on the internet. This skepticism is much more acute among Turkish-Cypriot users in 2014. Online victimization is generally low among internet users in Cyprus. Very few respondents reported having had their credit card details stolen via internet use, having been misled in their online purchases or having been bullied or harassed online in the past year. One in ten internet users in both communities reports having received obscene or abusive e-mails and about the same percentage of Greek-Cypriot users has been contacted by someone attempting to extort their bank or personal details. Accidentally arriving at pornographic content is more common, especially among Greek- Cypriots. The most frequent type of online victimization is receiving a virus. Violation of privacy online, a theme explored only in the 2014 survey, is uncommon among Cypriot internet users and, when it occurred, it was considered a minor problem. The majority of users in both communities seems to accept as a fact that privacy is compromised online. A clear majority of Greek-Cypriot users reports being concerned about violations of privacy by governments, corporations and other users and this concern is even deeper among Turkish-Cypriots. Most users in both communities state that they actively protect their privacy online and that they feel that they can control their privacy. Attitudes regarding internet-related political efficacy underwent a noticeable change over time. Most Greek-Cypriot users in 2008 and 2010 state that internet use is not related to an increase in citizens’ political power, stronger citizen voice regarding government actions, better understanding of politics and higher responsiveness by public officials. Fewer respondents shared these pessimistic attitudes in 2012 and 2014. The opposite trend is observed in the Turkish-Cypriot community in the 2012 and 2014 surveys: pessimistic attitudes regarding the internet’s ability to enhance political efficacy and the political system’s responsiveness have increased. The degree of self-reported freedom of political expression among Greek-Cypriot respondents clearly increased over time. Self-reported freedom of political expression online also increased from 2010 to 2014, yet most people tend to feel that it is not safe to openly discuss politics online. A growing majority of the respondents believes that citizens should be free to criticize their government and to express even extreme ideas online. Still, about half of the respondents state that the government must intensify the regulation of the internet. In the Turkish-Cypriot community, respondents express a significant degree of uncertainty, evident by the quite high percentage of respondents selecting the option "not sure" in many questions. There is a significant drop in the percentage of respondents who state that they enjoy freedom of political expression, from 2012 to 2014, and the same is true for online political expression. At the same time, there is decreasing support for the idea that citizens should be free to criticize their government or to openly express their ideas (even if extreme) online. Respondents in both communities are more skeptical than optimistic regarding the extent to which one can trust other people. Greek-Cypriots are slightly more skeptical than Turkish-Cypriots. Finally, regarding face-to-face socializing, the overwhelming majority of respondents in both communities spends time with close relatives on a daily basis and about half of the respondents (slightly more in the Turkish-Cypriot community) meet other relatives or friends and acquaintances a few times a week. Socializing with colleagues outside the work environment is not very common for Greek-Cypriots: the majority engages in such activities never or almost never. Social ties around work seem to be stronger among Turkish-Cypriots.
Keywords: Internet use; World Internet Project – Cyprus; Online communicative activity; Internet phone calls; Instant messaging; Greek-Cypriot community; Turkish-Cypriot community; Greek-Cypriot users